Implementation of digital archives using a dynamic archive information system - Diah Ayu Caroline; Bambang Ismanto; Lelahester Rina (Universitas Padjadjaran, 2022)
Archive structuring is sorting and combining archives according to type and use of archives for organization's benefit. Electronic filing systems are useful in facilitating the management of archives in organization. The study aimed to determine the implementation of the Dynamic Archival Information System or Sistem Informasi Kearsipan Dinamis (SIKD) at the Purwodadi Grobogan Regional Archives and Library Office. The research method was descriptive qualitative. The results showed that implementation of SIKD in dynamic archives at the Purwodadi Grobogan Regional Archives and Library Office began with document recording, archive control, distribution of archives, archive storage, and archive shrinkage. Archives are recorded in various methods consist of agenda books, control cards, and manuscripts. Archive control used are a control card system, spreadsheet introduction, and the SIKD framework application, which is equipped with a login. Distribution of archives used identification cards in SIKD after taking advantage of new developments and using conventional process combinations. Archive storage, both active and inactive records used the usual storage process that relied on the classification code recorded on the control card. This study concludes that the creation of the archives to archives shrinkage needs to be optimized. Due to the limited human resources of digital archive managers, not all dynamic archive files are digitized, and not all units can use the SIKD system due to website network problems. This study implies that the management of digital archives needs improvements in meeting the needs of those who require them at the Purwodadi Grobogan Regional Archives and Library Office.